An empirical examination regarding quality in higher education - YACHNA SURYAVANSHI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The majority of the excellence methods which are frequently employed in businesses have been modified and utilized to the field of teaching. In the current paper, it is suggested to approach the issue of excellence in higher education from a promotion standpoint, that is, by first understanding the requirements of the target audience through their views of excellence. The purpose of the essay is to evaluate the qualities of higher education from a range of perspectives, including those of close relatives, pupils, teachers, and businesses. Utilizing the input-processoutput structure, these quality characteristics are then categorized. With the help of the study's findings, an incorporated strategy which will include a range of high-quality practices to handle quality problems in higher learning is being proposed. The end goal is to raise the bar on quality